The nonlinear effect of consumer embarrassment on avoidance: A meta‐analysis - Ziegler, Alexander H.; Peloza, John; Vincent, Leslie H. (Journal of Consumer Psychology, 2026)
Abstract Despite longstanding assumptions that embarrassment leads to avoidance, empirical findings remain inconsistent. This meta‐analysis synthesizes 152 independent samples ( N = 64,374) to clarify when and how embarrassment motivates avoidance. Drawing on Protection Motivation Theory, we find a curvilinear effect, where avoidance is strongest in moderately intense, embarrassing situations, but diminishes when embarrassment is either too weak to prompt concern or so intense that the consequences of avoidance become too severe to risk. This pattern underscores that avoidance is most likely when individuals perceive a moderate threat and believe avoidance is effective. Moderator analyses reveal that this effect is stronger for product‐related vs. medical contexts, when others are present, when embarrassment is anticipated (vs. experienced), and in collectivist cultures. Comparisons with guilt and shame further demonstrate that embarrassment operates through distinct, socially driven appraisals. These findings reconcile inconsistent findings in the embarrassment literature and offer guidance for reducing harmful avoidance by aligning threat and coping appraisals to promote engagement with socially sensitive behaviors. Implications for theory and practice, as well as future research priorities, are discussed.